THE EFFECT OF NSFR, LCR, RRR, AND LDR ON CAR OF FOREIGN BANKS IN INDONESIA (Study on Foreign Banks in Indonesia for the Period 2018-2021) - Christopher Marcellino Tejosantoso; Erman Denny Arfinto; Foza Hadyu Hasanatina (Diponegoro Journal of Management, 2023)
ABSTRACT During the COVID-19 shock, banks have to absorb the impact of economic crisis by supplying vital credit to the corporate sector and households which affect the CAR of the banks. CAR represents the banks’ health and can be affected by several liquidity ratios such as NSFR, LCR, RRR, and LDR. This study aims to unravel the effect of NSFR, LCR, RRR, and LDR on Capital Adequacy Ratio (CAR) of foreign banks operating in Indonesia for the period 2018-2021. The sample used in this study consists of 20 foreign banks operating in Indonesia for the period 2018-2021. Multiple regression analysis method is used to analyze the effect of independent variables on the dependent variable. The results of this study show that NSFR, LCR, and RRR partially has a positive and significant effect on CAR. Meanwhile, partially LDR has a positive and insignificant effect on CAR. Simultaneously, NSFR, LCR, RRR, and LDR variables affect CAR of foreign bank operating in Indonesia. Based on Adjusted R Square, simultaneously NSFR, LCR, RRR, and LDR have an effect on the CAR by 81% while the remaining 19% is influenced by other variables that have not been studied